Bovine colostrum and cheese effect on resistance of enamel from acid attack seen from neutralization cariogenicity saliva and noncariogenic plaque formation - Susi, Sukmasari; Yenni , Hendriani; Neneng , Nurjanah (2011)
Objective: To determine neutralization pH of saliva and plaque after chewing cheese and gargling with bovine colostrum. Materials and method:Quasi eksperimental research pre and post test design. Accidental sampling done with the inclusion criteria is not allergic to milk and its products, has a white spot on caries prone areas, willing and able to cooperate in the research. Sample obtained were 25 children. Analysis saliva and plaque made after 5 minutes and 30 minutes chewing cheese and gargling bovine colostrum. Administration repeated every week until one month. Analysis used Mann-Whitney U. Results: In the first day, third week and 4th week, found no significance differences of pH saliva and plaque after 5 minutes minutes chewing cheese and gargling colostrum, however significance differences of pH saliva and plaque after 30 minutes minutes chewing cheese and gargling colostrum. In the 2nd week found no significance differences of pH saliva and plaque after 5 minutes and 30 minutes chewing cheese and gargling colostrum. Conclusion: Neutralization saliva and formation non-cariogenic plaque can be seen from pH saliva and pH plaque. The result showed that 5 minutes after cheewing cheese and gargling bovine colostrum have no effect to neutralization pH of saliva and plaque, however pH became neutral after 30 minutes.